Pengaruh Model Inquiry Based Learning (IBL) terhadap Hasil Belajar Siswa Kelas IV pada Mata Pelajaran Bahasa Indonesia di SDN 01 Seputih Jaya - Chairani; Siti Zulaikhah; Ayu Reza Ningrum (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Low student learning outcomes in Indonesian language, particularly on the topic of pantun (traditional Indonesian poetry), among fourth-grade students at SDN 01 Seputih Jaya were attributed to teacher-centered instructional practices, which limited students' opportunities to ask questions, engage in discussions, and independently construct knowledge. As a result, students' critical thinking skills and conceptual understanding had not developed optimally. This study aimed to determine the effect of the Inquiry-Based Learning (IBL) model on students' learning outcomes in Indonesian language, specifically on the topic of pantun, among fourth-grade students at SDN 01 Seputih Jaya. The study employed a quantitative approach using a quasi-experimental method with a Pretest–Posttest Control Group Design. The population consisted of all fourth-grade students at SDN 01 Seputih Jaya in the 2026/2027 academic year. A saturated sampling technique was applied, with Class IVA (18 students) assigned as the experimental group taught using the Inquiry-Based Learning model and Class IVB (20 students) as the control group taught using the Problem-Based Learning (PBL) model. The results of the Independent Samples t-Test revealed a significance value of 0.000 < 0.05 and a calculated t-value of 4.869, which exceeded the critical t-value of 2.028, indicating that the null hypothesis was rejected and the alternative hypothesis was accepted. Furthermore, the average N-Gain score of the experimental group was 0.74 (high category), while that of the control group was 0.27 (low category). These findings demonstrate that the implementation of the Inquiry-Based Learning model has a positive and statistically significant effect on the Indonesian language learning outcomes of fourth-grade students. Therefore, the model can serve as an innovative and effective instructional alternative for elementary school teachers.